Luteolin inhibits human prostate tumor growth by suppressing vascular endothelial growth factor receptor 2-mediated angiogenesis. - Poyil Pratheeshkumar (Public Library of Science (PLoS), 2012)
Angiogenesis, the formation of new blood vessels from pre-existing vascular beds, is essential for tumor growth, invasion, and metastasis. Luteolin is a common dietary flavonoid found in fruits and vegetables. We studied the antiangiogenic activity of luteolin using in vitro, ex vivo, and in vivo models. In vitro studies using rat aortic ring assay showed that luteolin at non-toxic concentrations significantly inhibited microvessel sprouting and proliferation, migration, invasion and tube formation of endothelial cells, which are key events in the process of angiogenesis. Luteolin also inhibited ex vivo angiogenesis as revealed by chicken egg chorioallantoic membrane assay (CAM) and matrigel plug assay. Gelatin zymographic analysis demonstrated the inhibitory effect of luteolin on the activation of matrix metalloproteinases MMP-2 and MMP-9. Western blot analysis showed that luteolin suppressed VEGF induced phosphorylation of VEGF receptor 2 and their downstream protein kinases AKT, ERK, mTOR, P70S6K, MMP-2, and MMP-9 in HUVECs. Proinflammatory cytokines such as IL-1β, IL-6, IL-8, and TNF-α level were significantly reduced by the treatment of luteolin in PC-3 cells. Luteolin (10 mg/kg/d) significantly reduced the volume and the weight of solid tumors in prostate xenograft mouse model, indicating that luteolin inhibited tumorigenesis by targeting angiogenesis. CD31 and CD34 immunohistochemical staining further revealed that the microvessel density could be remarkably suppressed by luteolin. Moreover, luteolin reduced cell viability and induced apoptosis in prostate cancer cells, which were correlated with the downregulation of AKT, ERK, mTOR, P70S6K, MMP-2, and MMP-9 expressions. Taken together, our findings demonstrate that luteolin inhibits human prostate tumor growth by suppressing vascular endothelial growth factor receptor 2-mediated angiogenesis.